(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, multi objective approach used for Optimal Location and Sizing (OPS) of Distributed Generation (DG) unit using Particle Swarm Optimization (PSO) algorithm. The objectives used are Voltage Profile Improvement Index (VPII) and Locational Marginal Price (LMP). In order to improve the voltage profile and to lessen the congestion above two objectives are combined and formulate the multi objective optimization (MOO) problem. To solve the MOO problem metaheuristic optimization technique called PSO has been used. It is verified on IEEE 14-bus system to illustrate the effectiveness of the PSO.